Thermodynamic and thermoeconomic aspects of utilizing two distinct solar collectors in a multigeneration system - Eman Shakir Hussein Hussein; Iraj Mirzaee; Samrand Rash-Ahmadi; Morteza Khalilian (International Journal of Thermofluids)
This thesis delves into the thermodynamic and exergoeconomic analysis of a multigeneration system that utilizes solar and geothermal energy to generate electricity, cooling, heating, hydrogen, and fresh water. The system's design comprises a solar collector, geothermal energy, an organic Rankine cycle, a double-effect lithium-bromide absorption refrigeration cycle, a domestic water heater, a proton exchange membrane electrolyzer, and a reverse osmosis desalination unit. Therminol VP1 nanofluid mixed with AL2O3 is utilized in the solar collector. The EES software was used to perform all the analyses. The research is centered on factors such as the concentration of nanoparticle volume, the temperature at the inlet of the solar collector, solar radiation, and the figure of merit of TEG. A comparison of PTC, ETC collectors indicates that the PTC collector demonstrates superior performance. The utilization of the PTC collector resulted in system energy and exergy efficiencies of 22.39 % and 15.11 %, respectively. Additionally, integrating the TEG unit will lead to a 50 % increase in power production by the system. In addition, the system can generate 56.6 kilograms of hydrogen per day and 1.47 kilograms of freshwater per second.